The 3D's of apoptosis: death, degradation and DIAPs. - Palaga, T.; Osborne, B. (Nature Cell Biology, 2002)
Inhibitor of apoptosis proteins (IAPs) are critical regulators of apoptosis. Recent evidence suggests that in some situations, induction of apoptosis initiates general repression of translation, as well as the targeted ubiquitination and degradation of IAPs.